Vertical undbundling, the coordination of investment, and network pricing - Gert Brunekreeft; Nele Friedrichsen (Jacobs University Bremen, Bremer Energie Institut, 2010)
This paper provides a formal analysis on the investment coordination problem in a vertically separated electricity supply industry, although the analysis may apply also to other network industries. In an electric- ity system, the investment decisions of network and power plants need to be coordinated. In unbundled markets, firm-internal coordination no longer applies. We develop a formal approach to examine whether sim- ple information exchange ("cheap talk") could restore coordination. We adopt a three-stage profit-optimized investment model, with a (regulated) monopoly network and two asymmetrical Cournot-type generators. To analyse credibility of cheap talk we apply the concept of self-signalling in a game with incomplete information and positive spillovers. We show that cheap talk cannot generally solve the investment coordination prob- lem and as a result separation may actually cause a costly coordination problem. We then examine locational network pricing as a coordination device to internalize the incentive problem.
Keywords: C72; D23; L22; L51; 330; cheap talk; unbundling; game theory; network; investment; coordination